Fighting lone mothers' poverty through in-work benefits - Methodological issues and policy suggestions - Pronzato, Chiara Daniela (Munich, 2013)
"Lone mothers are overrepresented among poor people in many European countries. In 1998, in Norway, a welfare reform increased the amount of benefits and introduced working requirements. Using a quasi-experimental model, Mogstad and Pronzato (2012) find a positive effect of the reform on lone mothers’ labour supply and a small reduction in poverty. Is the best result that policy makers could obtain in terms of poverty reduction? In this paper, I estimate a discrete choice model of earnings and welfare participation decisions, and use the behavioural estimates to derive the policy parameters which would have minimized poverty among lone mothers."